GAMBARAN RADIOLOGI VESIKOURETRA REFLUX - Rivan Kurniawan; Maryeti Marwazi; Nilas Warlem; Elfi Yulfienti (Nusantara Hasana Journal, 2026)
Vesicoureteral reflux (VUR) is a urological disorder characterized by the backflow of urine from the bladder into the ureter or kidney. It often causes recurrent urinary tract infections and may lead to renal damage. Radiological modalities, particularly CT urography and VCUG, play a key role in establishing the diagnosis. A 7-year-old boy presented with fever and recurrent urinary tract infections. CT urography revealed severe hydronephrosis and hydroureter on the right side, consistent with VUR. The patient was treated conservatively with prophylactic antibiotics and regular monitoring of renal function. Clinical improvement was achieved with conservative therapy. The prognosis is favorable with early diagnosis and long-term follow-up. Radiological imaging is essential for diagnosing VUR and guiding management. Conservative treatment with careful monitoring can provide good outcomes in pediatric patients.